PERILAKU SEKSUAL PRANIKAH MAHASISWA UNIVERSITAS “X” PELAKU CAM SEX DI KOTA SEMARANG - Mohammed Lukito Raja Puara; Priyadi Nugraha Prabamukti; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The total number of Indonesian internet users in 2017 was 143.26 million, an increase of 10.56 million in a year. Of the approximately 1.8 million Indonesians, 50% of them are unable to refrain from doing cybersex. Cybersex in terms of cam sex can be done remotely and can trigger premarital sexual behavior in adolescents. There were 26 cases of unwanted pregnancies and as many as 400 people with HIV / AIDS in Central Java, 70% of whom were adolescents who were affected by premarital sex in the 15-20 year age range in Semarang City. This study was to identify premarital sexual behavior of university